1983
DOI: 10.1111/j.1399-3054.1983.tb04165.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of temperature and moisture stress on the accumulation of abscisic acid in bean

Abstract: Levels of abscisic acid (ABA) and several indicators of leaf‐water status were measured in excised and intact primary leaves of bean (Phaseolus vulgaris cv. Kinghorn) exposed to different temperature and moisture regimes. After 2 h at 5°, 25° or 45°C under moist conditions, the water status of detached leaves showed only minor changes, and there was no increase in ABA. Under conditions favoring water loss, ABA rose over 10‐fold at 25°C, and trends towards higher ABA levels were observed at 5° and 45°C. When in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

1985
1985
2005
2005

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(10 citation statements)
references
References 19 publications
0
10
0
Order By: Relevance
“…Relative water content is a good and simple index of plant water status. Low temperature stress indirectly induces water stress (Eze et al, 1983); hence, the level of water stress induced by chilling can be measured by RWC. Chilling treatment decreased the RWC of S. guianensis , indicating that water stress occurred at low temperature.…”
Section: Discussionmentioning
confidence: 99%
“…Relative water content is a good and simple index of plant water status. Low temperature stress indirectly induces water stress (Eze et al, 1983); hence, the level of water stress induced by chilling can be measured by RWC. Chilling treatment decreased the RWC of S. guianensis , indicating that water stress occurred at low temperature.…”
Section: Discussionmentioning
confidence: 99%
“…Water imbalance is frequently accompanied by chilling stress Kabaki & Tajima 1981;Me William et al 1982;Wright & Simon 1973). The increase of ABA levels has been suggested to be caused by chilling-induced water stress (Eze, Dumbroff & Thompson 1982;Lalk & Dorffling 1985;Vemieri etal. 1991).…”
Section: Discussionmentioning
confidence: 99%
“…ABA is believed to play a role in plant tolerance to extreme environmental conditions (Salisbury and Marinos, 1985;Zeevaart and Creelman, 1988). Endogenous ABA accumulation in response to environmental stress has been shown in many plant species Eze et al, 1983;Skriver and Mundy, 1990;Zeevaart and Creelman, 1988). Many studies have demonstrated ABA accumulation during cold acclimation of plants and cold tolerance induction by exogenous ABA application (Bomman and Jansson, 1980;Chen and Gusta, 1983;Reaney et al, 1989).…”
mentioning
confidence: 99%